Statistical characteristics of high frequency gravity waves observed by OH airglow imaging from Tirunelveli (8.7°N) - Narayanan, V. Lakshmi; Gurubaran, S. (My University, 2013)
The importance of high frequency gravity waves in the upper mesospheric region is now well recognized. In this study, we examine the characteristics of high frequency gravity waves observed in OH emission by an all-sky airglow imager operated from Tirunelveli (8.7°N, 77.8°E) during 2007. Background wind information was obtained from co-located MF radar from which the intrinsic wave parameters were estimated. The study reveals predominance of meridionally propagating waves. The phase speeds of the waves were found to be relatively higher during equinoxes compared to solstices. Nearly half of the observed waves showed vertically evanescent behavior. We probed the relative importance of various terms in the gravity wave dispersion relation. We found that the contribution from the wind shear and curvature terms are not significant for statistical studies of high frequency wave events. Nevertheless, they may be important for case studies of individual wave events. Moreover, the analysis revealed the importance of wave reflections arising out of oppositely directed background winds for the short horizontal wavelength gravity waves. This could explain the observed predominance in the propagation towards the meridional directions.
Keywords: Quasi-monochromatic gravity waves; High frequency gravity waves; OH airglow imaging; Gravity waves; MF radar; Tirunelveli